Hubungan Pengetahuan Dan Perilaku Ibu Tentang Pencegahan Penularan Penyakit Malaria Di Desa Rampah Kecamatan Kutambaru Kabupaten Langkat Tahun 2022 - Meiyana S; Ninsah Mandala Putri Br Sembiring (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2023)
One of the infectious diseases that is still a public health problem is malaria. This study aims to determine the relationship between knowledge and behavior of mothers regarding the prevention of transmission of malaria in Rampah Village, Kutambaru District, Langkat Regency in 2022. The population in this study were all mothers who were in Rampah Village, Kutambaru District, Langkat Regency, totaling 325 people. Sampling using the Slovin formula with a total sample of 179 respondents, that there is a relationship between Mother's Knowledge about Prevention of Malaria Transmission in Rampah Village, Kutambaru District, Langkat Regency with p = 0.0003. p value = 0.000 (P > 0.05) this means that there is a relationship between Mother's Behavior regarding Prevention of Malaria Transmission in Rampah Village, Kutambaru District.